The efficiency of the education system in Kazakhstan: Programme for International Student Assessment (PISA) - Mailybaeva, G.S.; Nurgaliyeva, S.A.; Zhexembayeva, Zh.R.; Zholumbayeva, R.M.; Utegulov, D.E (Opción, 2019)
The goal of the article is to identify the real situation of the school students’ readiness in Kazakhstan for international examinations and appropriate recommendations on the professional use of the obtained results. This will provide a critical understanding of traditional ideas and for new designs and further development. During the study, methods of comparative analysis, system and logical analysis, a method of generalizing information were used. As a result, the authors proposed recommendations for improving the quality of educational process in educational organizations of the Republic of Kazakhstan, taking into account the requirements of international comparative studies.